"Tercerización de servicios colaterales para optimizar el proceso de construcción de departamentos en la ciudad de Trujillo - 2016." - Urbina Haro, Luis Emilio Manuel (2017)
ABSTRACT Construction companies today, are aware of their limitations, when it comes to carry out activities of great specialization, these companies do not have the staff who have such knowledge, only perform service work as a simple worker on the floor; Which is why the need arises to outsource several complementary services via outsourcing. For this study, one of the sources that we used was the Comprehensive Outsourcing Research thesis of the Universidad Católica del Perú - 2013, where it talks about the value chain and the chain of processes that allow to identify the diverse processes and procedures within a Company in the creation of a product with added value for the client. In the study we have worked with a sample universe made up of 25 workers from seven construction companies in Trujillo. For the investigation has been applied descriptive correctional design, which refers to the better the first variable, the better the optimization of the construction process. In conclusion, it can be affirmed that "the outsourcing of collateral services" have been maintained at a high level and has been very positive, because it allowed us to optimize the process of the construction of apartments in the city of Trujillo 2016. Therefore, it is recommended To the construction companies, make the contracting of tertiarizar companies to improve and optimize the constructions of departments in the city of Trujillo. Since these companies will reduce costs, improve and facilitate the work and that the tertiarizadoras companies will be in charge of collateral works like finishes, painting, veneers, also it was decided to recommend that they use the appropriate work contract. Pay overtime and qualify the staffs who are entitled to them and a number of benefits for both companies the builders and tertiarizers.